Candida parapsilosis: resistência as equinocandinas e a suscetibilidade a antifúngicos isolados e em combinação - Chassot, Francieli (2016)
Candida parapsilosis is a yeast fungus that causes a wide spectrum of infections predominantly in immunocompromised patients and representing a major cause of infections related to health care. The emergence of resistance of this species to echinocandins requires the search for new therapeutic options. In this context, this thesis aimed the exposure in vitro to increasing concentrations of echinocandins in C. parapsilosis echinocandin-suscetible (ES) to obtain C. parapsilosisis echinocandinresistant (ER) to then, evaluate the susceptibility in vitro of different strains of C. parapsilosis ES and ER, against antifungal agents (amphotericin B, fluconazole, flucitosine and voriconazole) and against the combinations between these drugs, as well as evaluate the antifungal properties of diphenyl diselenide (PhSe)2 and the ebselen. Additionally, the expression levels of the FKS gene for C. parapsilosis ES and ER were checked. The evaluation of in vitro susceptibility tests based on protocols M27-A3 and M27-S4 of CLSI showed that all strains C. parapsilosis ES and ER were susceptible to amphotericin B. The strains ES showed no resistance to antifungal agents tested and the rates of resistance to fluconazole, voriconazole and flucytosine were 73.3%; 43.3% and 20% for strains ER, respectively. Furthermore, exposure of C. parapsilosis to echinocandins generated cross-resistance and resistance in vitro to azoles and flucytosine. Associations between amphotericin B, flucytosine, fluconazole and voriconazole were assessed by microdilution checkerboard method and demonstrated that for C. parapsilosis ES and ER groups, the main interaction was the indifferent activity and, in many cases the high percentage of antagonism was observed for ER strains. Through susceptibility testing based on the protocol CLSI M27-A3, can be observed that the (PhSe)2 and ebselen exhibited antifungal activity in vitro against C. parapsilosis ES, with minimal inhibitory concentration (MIC) ranging from 1-8μg/mL and 0.25-4μg/mL, respectively. However, ebselen showed the best antifungal activity against the strains ER, with MICs ranging from 0.06-4μg/mL. Additionally, the verification of the gene expression levels FKS by Real Time PCR demonstrated that the emergence of resistance to echinocandins modifies the expression levels of the FKS gene in C. parapsilosis ER. In this context, exposure in vitro to increasing concentrations of echinocandins is an important factor for the emergence of resistance in C. parapsilosis, a phenomenon that brings consequences for the susceptibility profile of this species.